The Effects of Brand Image on Consumer Loyalty: The Role of Consumer Satisfaction and Brand Trust as Intervening Variables - Rini Kuswati; Wahyu Triyulianto Putro; Wafiatun Mukharomah; Muzakar Isa (Urecol Journal. Part B: Economics and Business, 2021)
This study aims to analyze the effect of brand image on consumer loyalty Telkomsel in the city of Surakarta with consumer satisfaction and brand trust as mediating variables. This study uses quantitative research methods, and sampling is carried out using non-probability methods. The number of respondents used was 167 respondents. This research uses SEM Smart PLS analysis method. The results showed that the variable (1) brand image had a positive and significant effect on customer satisfaction, (2) brand image has a positive and significant effect on brand trust, (3) customer satisfaction has a positive and significant effect on customer loyalty (4) brand trust has a positive and significant effect on consumer loyalty (5) consumer satisfaction has a positive and significant effect on brand trust, (6) brand image has a positive and significant effect on consumer loyalty. In addition, the variables of consumer satisfaction and brand trust significantly prove as mediate partially.